The first canine visceral leishmaniasis outbreak in Campinas, State of São Paulo Southeastern Brazil - Andrea Paula Bruno von Zuben; Rodrigo Nogueira Angerami; Claudio Castagna; Marisa Bevilacqua Denardi Baldini; Maria Rita Donalisio (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction Early detection of American visceral leishmaniasis (AVL) outbreak in animals is crucial for controlling this disease in non-endemic areas. Methods Epidemiological surveillance (2009-2012) was performed in Campinas, State of São Paulo, Brazil. Results In 2009, Leishmania chagasi was positively identified in four dogs. Entomological research and three serological studies (2010-2012) were undertaken as monitoring measures; these approaches revealed a moderate prevalence of Leishmania present in 4% of the canine population. Nyssomyia whitmani and Lutzomyia longipalpis were the predominant species identified. Conclusions Detection of an AVL outbreak in dogs in an area with an evolving natural landscape containing sand flies is crucial for control programs.